FAKTOR RISIKO KEJADIAN OBESITAS PADA IBU BALITA DI DESA LOKUS PENANGGULANGAN STUNTING (STUDI DI DESA KEMBANGAN KECAMATAN BONANG KABUPATEN DEMAK PROVINSI JAWA TENGAH) - Ma'rifah Tri Citra; Apoina Kartini; Suyatno Suyatno (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Obesity in Indonesia is increasing from year to year. One potential contributor to obesity is women. The purpose of this study was to determine the risk factors for the incidence of obesity in mother of toddler in the Locus of Stunting Prevention. It was an observational analytic study with a case control method. The sample used was 106 mother of toddler consisting of 53 obesity woman and 53 non obesity woman was used 24 hour recall method of nutritional consumption and 24 hour recall of physical activity. Bivariat analysis showed that factors related to the incidence of obesity in mother of toddler were low levels of knowledge (OR = 9,260; CI = 3,529 - 24,300), parity ≥ 2 children (OR = 2,506; CI = 1,058 - 5,953), genetics (OR = 3,160; CI = 1,342 - 7,440), low physical activity (OR = 3,052; CI = 1,267 - 7,374), more energy adequacy level (OR = 10,217; CI = 3,727 - 28,0101), higher protein adequacy level (OR = 4,276; CI = 1,818 - 10,058), more fat adequacy level (OR = 8,135; CI = 2,975 - 22,245), and more carbohydrate adequacy level (OR = 16,734; CI = 3,674 - 76,227). Unrelated in this study are low education, exclusive breastfeeding, use of hormonal contraception, and per capita income.Multivariat analysis showed knowledge is the most related risk factor for the incidence of obesity for mother of toddler.It is expected that the Bonang I Health Center in collaboration with the a to socialize the effects, and ways to prevent obesity, to improve the level of health in Kembangan Village.